Design a mould insert for a complex design - Saminathan Govindasamy, Mugilvarnan Saminathan; Ibrahim, Halim Irwan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Cycle time of a part in injection moulding process is very important as the rate of production and the quality of the parts produced depends on it, whereas the cycle time of a part can be reduced by reducing the cooling time which can only be achieved by the uniform temperature distribution in the moulded part which helps in quick dissipation of heat and locating a proper gate system[1]. The aim of the project is to design and conduct simulation using SolidWorks 2019 and Autodesk Moldflow Advisor software of a mould insert for car piston head material for injection moulding. The project focuses on incomplete filling and warping which caused by the gate location and cooling channel of the mould insert. Two types of gate locations were tested in this project. The purpose of designing this mould is to improve the reliability and productivity during injection moulding process by reducing the cycle time of the part in the injection moulding. This was analysed using Autodesk Moldflow Advisor and finished model was designed in SolidWorks 2019 software. The gate location was affecting the fill time, quality prediction, time to reach ejection temperature, weld line, as well as injection pressure. The cooling channel was tested for volumetric shrinkage. In Autodesk, fill + pack, cool analysis and warp were analysed in the simulation. The gate location and cooling system effects the part quality of a mould insert.